Multiple Digital Image Encryption Algorithm Based on Chaos Algorithm - Zhang, Ying; He, Yi; Zhang, Jing; Liu, Xiaobo (Mobile networks and applications, 2022)
In this study, a multiple digital image encryption algorithm based on chaos algorithm is presented. The cyclic matrix is constructed by logical mapping, and sparse transformation of plaintext image is realized by discrete cosine transform (DCT). The gray image of DCT is measured, and several digital images are merged. Lorenz chaotic system and logistic map are adopted to generate chaotic key sequence related to plaintext image features, replace pixel value, scramble pixel position, diffuse image, and finally obtain ciphertext image. It encrypts many kinds of digital images. The proposed encryption algorithm has excellent image encryption effect and high security.